(untitled) (Experimental biology, 2015)
Infl uence of ouabain to the P-selectin expression on the surface of neurovascular endotheliocytes under exposure of amyloid- β was investigated in this research. It was shown that ouabain activate endocytosis and regulate amount of Pselectin on the cell surface.